Koga in zakaj stiska primež globalizacije? - Svetličič, Marjan (Družboslovne razprave, 2008)
What are globalisation's impacts on the position of workers and capital, on wages and employment and who is responsible for the assumed growth in inequalities as a result of globalisation in general and particularly of work are the issues examined in this article. The theoretical framework sets the analytical basis for the subsequent empirical evaluation of the issues. Traditional theories are unable to explain current movements of wages and the relations between labour and capital in either developed or developing countries. Modern theories show that technology, falling demand for unskilled labour and changes in international trade (intermediate products..) are some of the explanations for the growing inequalities and changing relations between labour and capital. The strength of the squeeze brought about by globalisation depends on objective (technology developments, structural changes...) and subjective factors (strategies, policies) and is therefore not something which cannot be managed.
Keywords: Globalisation; Globalizacija; globalization; Teorije; Theories; Plače; Salaries; Brezposelnost; Unemployment; Srednji razredi; Middle classes; Technological development; Tehnološki razvoj; ekonomski razvoj; delavci; srednji razred